Delayed Onset of Central Diabetes Insipidus With Ketamine Sedation: A Report of 2 Cases. (April 2021) - Herity, Leah B.; Baker, Cassandra; Kim, Christin; Lowe, Denise K.; Cahoon, William D.
Ketamine is being prescribed with greater frequency due to an emphasis on multimodal analgesia. With increasing use, uncommon adverse effects associated with ketamine are likely to surface. Limited reports of transient central diabetes insipidus (DI) occurring early after initiation (ie, within 10 hours) of ketamine have been reported. We present 2 cases of delayed onset (32 hours or more after initiation), ketamine-induced, transient central DI in patients cannulated for venovenous extracorporeal membranous oxygenation. No other causes of central DI were determined based upon physical examination or laboratory data, and both patients responded to treatment with desmopressin/vasopressin. The Naranjo adverse drug reaction probability scale noted a probable causation for each case. These cases demonstrate the possibility of a rare but serious complication of ketamine. Improvement after discontinuation of ketamine and administration of desmopressin/vasopressin appear to support a drug–effect association.